Motion control using voice for wheelchair application - Ismail, Hashimah (2006)
This paper describes the significant design to build a voice-controlled wheelchair. This project is intended to increase the ease of mobility for disabled/injured people. The design would allow these people to live more independently. Presently, people use blow-tubes or chin-joysticks to control motorized wheelchairs. Speech recognition is a prominent technology which can give an alternative to people to interact with machines or devices especially to those who are quadriplegics. We have resolved the disabled problems by implementing voice control interfacing, over a microphone, for the wheelchair. In this project, the manual wheelchair has been modified so that it can be actuated by two DC motors. The motions of the wheelchair are then controlled by the verbal instructions of the user. The results show that the design is applicable and feasible. The speech processing can be done in real-time and is therefore deemed a viable alternative to present methods of motorized wheelchair control. The design and the analysis of the project are presented in this report